Hierba entre las grietas (2023)
The essay "Grass Between the Cracks" explores the relationship between culture, identity and space through an artistic proposal. Use the metaphor of Pandora's box to introduce the art project, which seeks to explore the objects and signs present in the daily life of the city ​​of Bogota. Inspired by the idea that the objects and configurations that arise in the domestic environment carry with them an emotional charge, I decided to analyze patterns of habits and singularities found in representative places.